Resting state arousal and functional connectivity in autism spectrum disorder - Kleberg, Johan Lundin (J Neurophysiol, 2014)
A recent study (Eilam-Stock T, Xu P, Cao M, Gu X, Van Dam NT, Anagnostou E, Kolevzon A, Soorya L, Park Y, Siller M, He Y, Hof PR, Fan J. Brain 137: 153–171, 2014) demonstrated that resting state electrodermal activity is correlated with different patterns of brain activity in subjects with autism spectrum disorder (ASD) than in typical controls. These results are considered in light of theories of atypical arousal in ASD.